2014
DOI: 10.1039/c4md00147h
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions of ASPP2: an emerging therapeutic target

Abstract: ASPP2 induces apoptosis and is downregulated in many types of cancer, making it a promising target for anti-cancer drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…We have previously shown that ASPP2 693–918 is intrinsically disordered and is involved in ASPP2 intramolecular interactions between the Pro-rich and Ank-SH3 domains that regulate various ASPP2 interactions with other proteins . Together, ASPP2 331–692 and ASPP2 693–918 comprise a vast intrinsically disordered region, connecting the structured termini of ASPP2 that mediate numerous interactions important for ASPP2 functions . That CagA evolved to interact with the intrinsically disordered regions of ASPP2 that mediate fewer (i.e., two) known interactions, and not the structured termini that mediate many known interactions, may be important for its function to inhibit transformed host cells from proceeding with their intended apoptotic program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that ASPP2 693–918 is intrinsically disordered and is involved in ASPP2 intramolecular interactions between the Pro-rich and Ank-SH3 domains that regulate various ASPP2 interactions with other proteins . Together, ASPP2 331–692 and ASPP2 693–918 comprise a vast intrinsically disordered region, connecting the structured termini of ASPP2 that mediate numerous interactions important for ASPP2 functions . That CagA evolved to interact with the intrinsically disordered regions of ASPP2 that mediate fewer (i.e., two) known interactions, and not the structured termini that mediate many known interactions, may be important for its function to inhibit transformed host cells from proceeding with their intended apoptotic program.…”
Section: Resultsmentioning
confidence: 99%
“…24 Together, ASPP2 331−692 and ASPP2 693−918 comprise a vast intrinsically disordered region, connecting the structured termini of ASPP2 that mediate numerous interactions important for ASPP2 functions. 8 That CagA evolved to interact with the intrinsically disordered regions of ASPP2 that mediate fewer (i.e., two) known interactions, and not the structured termini that mediate many known interactions, may be important for its function to inhibit transformed host cells from proceeding with their intended apoptotic program. This mode of interaction could enable ASPP2 to interact with p53, via its Ank-SH3 domain, without competing for CagA binding.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptosis-stimulating proteins of the p53 (ASPP) family, which are identified as regulators of the tumor suppression function of p53, is compose of three members, ASPP1, ASPP2, and iASPP [ 84 ]. ASPP2 binds to various proteins that regulate apoptosis, cell polarity, proliferation, and differentiation [ 85 , 86 ]. p53 is a member of a family of three proteins: p53, p63, and p73.…”
Section: Aspp2 In Endometriosis and Endometrial Cancermentioning
confidence: 99%
“…The ASPP proteins interact with different apoptosis-related proteins such as the p53 protein family, Bcl2 and NFκB 2 7 13 20 21 22 23 24 . iASPP Pro interacts with iASPP Ank-SH3 in cells and phosphorylation of iASPP by B1/CDK1 on S84 and S113 inhibits this interaction 25 .…”
mentioning
confidence: 99%